A First‐Principles Study of Electronic Properties of Twisted MoTe2. Issue 3 (12th November 2019) - Wu, Jiafang; Meng, Lijun; Yu, Jun; Li, Yizhi
Abstract : The electronic properties of the twisted transition metal dichalcogenide MoTe2 through first‐principles calculations are investigated. The interlayer interaction is corrected by van der Waals correction. Some local stable twisted configurations are obtained by calculating the interlayer binding energy as a function of twist angle. The calculations indicate that the size of bandgap is dependent on the twist angle, and a transition from indirect to direct bandgap semiconductor is identified for both bulk and bilayer twisted 2H‐MoTe2 . The uniaxial compression significantly changes the bands and results in a phase transition from the original semiconductor to metal. Under uniaxial tensile, the valence‐band maxima (VBM) change from the Brillouin zone (BZ) center point Γ to the BZ face center point M. Interestingly, a phase transition from the semiconductor to metal is identified under both biaxial compression and tensile. The VBM, conduction‐band minima, and the orbital components around the Fermi level demonstrate a dramatic change under biaxial strain, which leads to a great change in optical and electronic transport properties of twisted MoTe2 . These results are useful for the understanding of the electronic properties of twisted systems and the applications of twisted layered materials in future electronic devices. Abstract : The electronic properties of the twisted transition metal dichalcogenide MoTe2 are studied by the first‐principles method. The size of the bandgap is dependent on the twist angle, and a transition from indirect to direct bandgap semiconductor is identified for both bulk and bilayer twisted 2H‐MoTe2 .